Komparasi empat jenis primer molecular sexing pada famili burung berbeda: Comparison of four types molecular sexing primers in different bird families - Fauziah Fitriana; Dian R. Setyorini; Clara A. Artdita; Risa Ummami; Aris Haryanto; Fatkhanuddin Aziz (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2023)
Determination sex of birds by the Polymerase Chain Reaction (PCR) method is increasingly popular among researchers and the public. The PCR method is known to provide accurate test results in determining the sex of birds, but one of its successes is greatly influenced by the compatibility between the primers used and the template DNA. This study was conducted to evaluate the use of primers 2550F/2718R, 1237L/1272H, P2/P8, and CHD1F/CHD1R in birds from the families Phasianidae, Estrildidae, Passeridae, and Psittacidae. PCR sexing was performed on DNA samples from the 4 bird families above, using primers 2550F/2718R, 1237L/1272H, P2/P8, and CHD1F/CHD1R. PCR results were evaluated by comparing the size of the PCR band with a reference. The results showed that the CHD1F/CHD1R primer could be used in 4 families tested. PCR products for male birds showed 1 band measuring approximately 500 bp, while for female birds 2 bands were 500 and 320 bp. Primer 2550F/2718R could only be used in the families Phasianidae and Psittacidae, while 1237L/1272H and P2/P8 could not be used in the samples tested. CHD1F/CHD1R primers can be used to determine the sex of birds from the families Phasianidae, Estrildidae, Passeridae, and Psittacidae.